PERAN LEMBAGA NAHDLATUL ULAMA DALAM MENINGKATKAN AKTIVITAS DAKWAH DI KOTA JAMBI PROVINSI JAMBI - Jesika Putri, Salsabilla; Yunus, Abdullah (Qaulan Baligha: Jurnal Ilmu Manajemen Dakwah, 2025)
This study discusses the role of the Nahdlatul Ulama (NU) Institution in increasing da'wah activities in Jambi City, Jambi Province. Da'wah is an important element in strengthening Islamic values ​​and building religious awareness in society. NU, as the largest Islamic organization in Indonesia, has a strategic role in spreading Islamic teachings through various programs and socio-religious activities. By using a qualitative approach to the phenomenological method, this study found that NU's role in increasing da'wah activities was carried out through an emotional approach in interactions with religious and community leaders, consistency in establishing relationships, and implementing socio-religious activities. The obstacles faced include limited human and financial resources, as well as challenges in dealing with differences in the background of community organizations. The results of this study emphasize the importance of strong leadership and effective communication strategies in increasing the effectiveness of NU's da'wah.